2014
DOI: 10.1007/s00418-014-1217-y
|View full text |Cite
|
Sign up to set email alerts
|

Progress in quantitative single-molecule localization microscopy

Abstract: With the advent of single-molecule localization microscopy (SMLM) techniques, intracellular proteins can be imaged at unprecedented resolution with high specificity and contrast. These techniques can lead to a better understanding of cell functioning, as they allow, among other applications, counting the number of molecules of a protein specie in a single cell, studying the heterogeneity in protein spatial organization, and probing the spatial interactions between different protein species. However, the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
80
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 83 publications
0
80
0
4
Order By: Relevance
“…SMLM data consist of the localizations of individual photoactivatable or photoswitchable fluorescent molecules. Therefore, a variety of methods have been developed to identify and characterize clusters of such localizations (12,13). These methods are often applied to investigate clusters of receptors in the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…SMLM data consist of the localizations of individual photoactivatable or photoswitchable fluorescent molecules. Therefore, a variety of methods have been developed to identify and characterize clusters of such localizations (12,13). These methods are often applied to investigate clusters of receptors in the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Before proceeding further, we note that it is possible that the image processing and localization algorithms used can also introduce errors in quantification, however this is treated in detail elsewhere [45,46]. A brief introduction to the quantitative measures being mentioned can be found in [7,47].…”
Section: Challengesmentioning
confidence: 99%
“…Recent reviews on the updates on the technology and its uses can be found in [4,5]. SMLM can potentially be used for quantitative measurements [6,7], e.g., in counting the number of molecules of a protein specie [8] and stoichiometry estimation of protein complexes [9][10][11], characterizing the spatial distribution of a protein specie [12][13][14][15], estimating the co-localization or co-clustering between organelles and also single molecules (SM) [16][17][18][19], estimating the relative positions of various components in a protein complex with high precision [20,21], and estimating the diffusion coefficients by means of single particle tracking (SPT) in a dense sample [22,23]. Two basic variants of SMLM are Photo-Activated Localization Microscopy (PALM) and STochastic Optical Reconstruction Microscopy (STORM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the topic is surveyed in two "review articles" and in seven "Original articles. "Hendrik Deschout, aleksandra radenovic, and their colleagues (Deschout et al 2014) review recent progress in single-molecule resolution microscopy with emphasis on quantitative measurements such as counting of single molecules (i.e., NMDa receptors, glycine-gated channels, and asialo-glycoprotein receptor) with PalM, analysis of heterogeneity in the spatial organization of general membrane proteins or networks of signaling receptors and nuclear pore complexes, and single-molecule colocalization involving dual-color super-resolution microscopy to analyze, for example, protein-protein interactions. Both the potential of the technique and currently existing problems (i.e., limited detection efficiency, overcounting due to photoblinking, sample drift, localization uncertainty, and photoconversion efficiency of fluorescent proteins) using these tools are evaluated.…”
mentioning
confidence: 99%